2003
DOI: 10.1055/s-2003-40707
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Transform Infrared Spectrometry Determination of the Metabolic Changes During a Maximal 400-Meter Swimming Test

Abstract: We describe the metabolic changes in the blood that appeared during a maximal 400-m swimming test in 7 male swimmers by Fourier-transform infrared spectrometry (FT-IR spectrometry). A 400-m test (255.9 +/- 6.8 s) was performed during which stroke frequency and time to complete each pool distance were recorded. In three other tests, the first 100 m, 200 m, and 300 m were swam at the same stroke frequency and velocity. Capillary blood samples were taken at rest and after tests to analyze change in plasma content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The study that reported the poorest test (≈378 s) (46) assessed male junior swimmers. Furthermore, only in five studies (9,52,54,55,58) swimmers reached swimming speeds over 1.50 m•s −1 ; however, the swimmers of these cited studies were of optimal technical level. Therefore, more studies are needed to include highperformance swimmers and separated groups to perform analysis of performance (e.g., technical level, genders, and competitive categories), and to verify which performance parameters reflect the actual performance.…”
Section: Discussionmentioning
confidence: 96%
“…The study that reported the poorest test (≈378 s) (46) assessed male junior swimmers. Furthermore, only in five studies (9,52,54,55,58) swimmers reached swimming speeds over 1.50 m•s −1 ; however, the swimmers of these cited studies were of optimal technical level. Therefore, more studies are needed to include highperformance swimmers and separated groups to perform analysis of performance (e.g., technical level, genders, and competitive categories), and to verify which performance parameters reflect the actual performance.…”
Section: Discussionmentioning
confidence: 96%